THE ADDITION VARIOUS LEVELS OF FRESH MAGGOT ON PRODUCTIVITY AND PHYSICAL QUALITY OF DUCK EGGS - Hidayatullah, Syarif; Sunu, Prayogi; Wulandari, Eudia Christina (Tropical Animal Science, 2022)
One of the areas of business that is widely cultivated by the community is livestock, besides that, seen from the results of livestock business, which is easy to market and is a daily need for the community, eggs are eggs. Egg production and quality are indicators of the economic value of poultry farming. It is important to conduct research and research on duck egg quality and production to determine the genetic ability of ducks and to provide excellent quality food from livestock. The purpose of this study was to determine the effect of using maggot on changes in the quality of duck eggs. This research was conducted using a completely randomized design (CRD) method which used 4 treatments and 5 replications, each treatment filled with 3 ducks. In this study feed rations used BSF maggot rations with different feedings in each treatment level (P0: 100% prepared feed, P1: 5% fresh maggot + 100% prepared feed, P2: 10% fresh maggot + 100% finished feed, P3: 15% fresh maggot + 100% finished feed) this research was conducted for 40 days and the first 10 days was the adaptation period of livestock to ad libitum feeding treatment. In the research data collection was carried out on days 38,39 and 40 in each treatment and replication. From the results of the study, it was found that there was no significant change in any research parameters (P>0.5), but the daily egg production quality and egg quality were very good and higher than previous studies.